Understanding the Effectiveness of Google's Organizational Design in Pursuing Sustainable Innovation - Kusumaningtyas, Rahma Pramudyawardani (Kreatif Publisher, 2024)
This paper explores the effectiveness of Google’s organizational design in fostering sustainable innovation. The challenge of achieving and maintaining continuous innovation, crucial for developing new business models and products, is a significant concern for many companies. Historical evidence suggests that organizations often lose their innovative edge over time despite initial successes. Assessing innovation capability involves evaluating a company’s success in product launches and its capacity to learn from failures and persist in its innovation efforts. From a firm-level perspective, the characteristics of an organization, including its structure, culture, and processes, are critical for sustaining innovation in rapidly changing industries. Google exemplifies a company that has consistently demonstrated its ability to innovate. Its matrix organizational structure, which promotes flexibility and cross-divisional collaboration, enhances its capacity for continuous innovation. Google’s organizational culture supports this with practices that encourage creativity and employee satisfaction, such as allowing pets at work and providing on-site childcare. By balancing internal and external collaboration, Google effectively sustains its innovative edge, showcasing the importance of a supportive organizational framework and culture in achieving long-term success.